Odpowiedzi

2009-12-08T18:24:10+01:00
10-2x[(-1,6)+(-19,5):(-2½)]=
10-2x[-1,6-19,5:(-2,5)]=
10-2x[-1,6+48,75]=
10-2x[47,15]=
10-94,3= 84,3
(-2,4x1,7=4,28):(2,75-3.45)= --- tutaj nie wiem o co chodzi z tym rowna sie
2009-12-08T18:23:42+01:00
10-2x[(-1,6)+(-19,5):(-2½)]=8x[(-21,1):(-2½)]=8x(-8,44)=(-67,52)
(-2,4x1,7=4,28):(2,75-3.45)=(-4,08+4,28):(-0,7)=0,2:(-0,7)=-0,285
2009-12-08T18:29:06+01:00
10-2x[(-1,6)+(-19,5):(-2½)]= 10-2x[-1,6 + 7,8]=
= 10 + 3,2x - 15,6x=
= 10 - 12,4x

a w drugim przykładzie to powinno być chyba 1,7+4,28 a nie 1,7=4,28